AI and Neuromarketing – Understanding Consumer Decision Making with Artificial Intelligence – Systematic Review - Deckker, Dinesh; Subhashini Sumanasekara (Indonesian Journal of Business Analytics, 2025)
Neuromarketing studies human behavior through artificial intelligence (AI) technologies, which allow scientists to use advanced analytical methods with data-based techniques. The paper systematically analyzes how AI functions in neuromarketing, including research about subconscious consumer assessment, predictive behavioral patterns, and in-the-moment biometric measurements. The study examines four leading AI technologies, machine learning, deep learning, natural language processing, and computer vision, to show their value in enhancing traditional marketing theory development and decision-making models. Future research must conduct time-based studies about AI's impact on consumer actions and create dependable ethical methods to manage responsible AI deployment. Every stakeholder in neuromarketing research, including marketers and policymakers, will find helpful information about AI innovation in this field within this review.